WADAH MUSIK INDIE LOKAL - Yohanes Rheza; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2020)
Individualism is one of the issues that occur in people's lives. One of the causes is one’s habit in spending most of their time working and resting at home and without social activities that can be done every day with other individual, furthermore with the existence of social media that makes humans able to communicate with electronic devices and not meeting directly. The main issue is